Marine Peptides and Related Compounds in Clinical Trial+ - Rawat, Diwan S.; Joshi, Mukesh C.; Joshi, Penny; Atheaya, Himanshu (Anti-Cancer Agents in Medicinal Chemistry, 2006)
Advances in the sophisticated instruments for the isolation and characterization of marine natural products, and development in the biological assay systems, have resulted in the discovery of various compounds of biomedical application. Marine natural products have been a source of new leads for the treatment of many deadly diseases such as cancer, acquired immuno-deficiency syndrome (AIDS) etc. The compounds of marine origin are diverse in structural class from simple linear peptides to complex macrocyclic polyethers. Number of marine peptides have been isolated in recent years which exhibit potent biological activities, and many of the compounds showed promising anticancer activity. Didemnin was the first marine peptide that entered in human clinical trials in US for the treatment of cancer, and other anticancer peptides such as kahalalide F, hemiasterlin, dolastatins, cemadotin, soblidotin, didemnins and aplidine have entered in the clinical trials. Clinical status of anticancer marine derived peptides have been discussed and reviewed.
Keywords: Didemnins